Patterns of care and dropout rates from outpatient mental healthcare in low-, middle- and high-income countries from the World Health Organization's World Mental Health Survey Initiative. Issue 12 (28th September 2021) - Fernández, Daniel; Vigo, Daniel; Sampson, Nancy A.; Hwang, Irving; Aguilar-Gaxiola, Sergio; Al-Hamzawi, Ali O.; Alonso, Jordi; Andrade, Laura Helena; Bromet, Evelyn J.; de Girolamo, Giovanni; de Jonge, Peter; Florescu, Silvia; et al.
Abstract: Background: There is a substantial proportion of patients who drop out of treatment before they receive minimally adequate care. They tend to have worse health outcomes than those who complete treatment. Our main goal is to describe the frequency and determinants of dropout from treatment for mental disorders in low-, middle-, and high-income countries. Methods: Respondents from 13 low- or middle-income countries ( N = 60 224) and 15 in high-income countries ( N = 77 303) were screened for mental and substance use disorders. Cross-tabulations were used to examine the distribution of treatment and dropout rates for those who screened positive. The timing of dropout was examined using Kaplan–Meier curves. Predictors of dropout were examined with survival analysis using a logistic link function. Results: Dropout rates are high, both in high-income (30%) and low/middle-income (45%) countries. Dropout mostly occurs during the first two visits. It is higher in general medical rather than in specialist settings (nearly 60% v. 20% in lower income settings). It is also higher for mild and moderate than for severe presentations. The lack of financial protection for mental health services is associated with overall increased dropout from care. Conclusions: Extending financial protection and coverage for mental disorders may reduce dropout. Efficiency can be improved by managing the milder clinical presentations at the entry point to the mental health system, providing adequate training, support and specialist supervision for non-specialists, and streamlining referral to psychiatrists for more severe cases.